Ranging Behavior of Genus Macaca in Disturbance Habitat: A Review - M. Ubaidilah Hasan; Abdu Rohman; Hikmah Buroidah; Muhamad Khoirul Anwar (Departemen Biologi, Institut Pertanian Bogor, 2026)
Numerous studies examined the effects of human disturbance on the home ranges of mammals, reptiles, and birds. Primates adjusted home range size according to habitat characteristics. However, there is a lack of reports that synthesize the ranging behavior across primate species under anthropogenic pressure. To facilitate our understanding, this study reviewed the literature on the ranging behavior of the genus Macaca in areas affected by various human disturbances. We found 41 reports, published between 1989 and 2025, that covered locations across regional areas from Asia, Africa, and Europe. The home ranges of the genus Macaca, which involved 15 macaque species, were documented as being impacted by human settlement, followed by agriculture and habitat degradation. The macaque species whose home range included human settlements and agricultural areas adopted smaller home ranges in response to provisioning food and crops, respectively. Meanwhile, the macaques tended to avoid areas exhibiting high levels of habitat degradation, expanding their home range in response to intensive logging. Our review provided important information to consider the anthropogenic impact in developing conservation management.